AKTIVITAS ANTI RAYAP MINYAK ATSIRI DARI KULIT JERUK Citrus nobilis var.microcarpa TERHADAP RAYAP TANAH Coptotermes curvignathus Holmgren - bu, Na; Diba, Farah; Dirhamsyah, M. (Universitas Tanjungpura, 2015)
Coptotermes curvignathus Holmgren is an urban pest which builds carton nests in dark places. This termite is difficult to control due to difficulties of direct spraying to entire colony. The new methods for control subterranean termites such as used the essentials oil is a prospective study. This study aims to determine the bioactivity of essential oil of orange peel Citrus nobilis var .microcarpa and to determine the optimal level of inhibiting termites C. curvignathus. Essential oil made from peel of C. nobilis orange which macerated with methanol for 24 hours. Essential oil obtained was dissolved on filter paper at a dose of 0.1 ml; 0.2 ml; 0.3 ml; and 0.4 ml. Then this filter paper used to biossay to determine the effectiveness of essential oil to inhibited subterranean termites C. curvignathus. This process was conducted in three days. The results showed that the highest activity which caused 100% mortality of termite was obtained at dose 0.4 ml. The greater dose of essential oils of orange peel resulted in the highest mortality of termites and vice versa resulted the lowest percentage of paper weight loss. The optimal dose in the use of essential oils of orange peel of C. nobilis to inhibited the termites C. curvignathus was 0.2 ml. Keyword: Anti-termitic activities, essential oil, Citrus nobilis var. microcarpa, Coptotermes curvignathus Holmgren